E-006 Carotid artery revascularization using the walrus balloon guide catheter: safety and feasibility from a US multicenter experience. (23rd July 2022) - Salem, M; Kvint, S; Baig, A; Monteiro, A; Cortez, G; Luisa Kuhn, A; Goren, O; Dalal, S; Jankowitz, B; Choudhri, O; Raper, D; Tanweer, O; et al.
Abstract : Introduction: The Walrus Balloon Guide Catheter (BGC) is a new generation of BGC, designed to eliminate conventional BGC limitations during mechanical thrombectomy (MT). We report a multi-institutional experience using this BGC for proximal flow-control (PFC) in the setting of carotid artery angioplasty/stenting (CAS) in elective (eCAS) and tandem strokes (tCAS). Methods: Prospectively maintained databases at 9 North-American Centers were queried to identify patients with cervical carotid disease undergoing eCAS/tCAS with Walrus BGC. Results: 110 patients (median age 68, 64.6% males) undergoing 80 eCAS (72.7%) and 30 tCAS (27.3%) procedures were included (median cervical carotid stenosis 90%; 41.8% with contralateral stenosis). Utilizing proximal flow-arrest technique in 87.2% and flow-reversal in 12.8% of procedures, the Walrus was navigated into the common carotid artery (CCA) successfully in all cases despite challenging arch anatomy (28.2%), with preferred femoral access (93.6%) and in monitored anesthesia care (81.8%). Angioplasty and distal embolic protection devices (EPD) were used in 83.7% and 52.7% of procedures, respectively. tCAS led to a mTICI 2b/3 in all cases. Periprocedural ischemic stroke (till 30-days post-operatively) rate was 0.9% and remote complications occurred in 1.8% of the cases. Last follow-up mRS of 0–2 was seen in 95.3% of eCAS cohort, with no differences in complications in the eCAS subgroup between PFC only versus PFC and distal EPD (median follow-up 4.1 months). Conclusion: Walrus BGC for proximal flow-control is safe and effective during eCAS and tCAS. Procedural success was achieved in all cases, with favorable safety and functional outcomes on short term follow-up. Disclosures: M. Salem: None. S. Kvint: None. A. Baig: None. A. Monteiro: None. G. Cortez: None. A. Luisa Kuhn: None. O. Goren: None. S. Dalal: None. B. Jankowitz: None. O. Choudhri: None. D. Raper: None. O. Tanweer: None. P. Jabbour: None. R. Starke: None. E. Levy: None. C. Griessenauer: None. A. Puri: None. R. Hanel: None. A. Siddiqui: None. J. Burkhardt: None.